Cele i narzędzia polityki pieniężnej w Polsce w warunkach kryzysu - Jaźwiński, Ireneusz (Goals and Tools of Monetary Policy in Poland Under Crisis Conditions, 2009)
Monetary policy is holding a very important position in a system of economic policy. In our times, a global financial and economic crisis is recognised to be a significant determinant of a whole economic policy, and the policy becomes focused on limitation of the crisis effects. Under these conditions the evolution of the monetary policy takes place in Poland, in particular of its goals and tools. The study introduces the essence of monetary policy in the context of its goals and tools as well as the changes in goals and tools of this policy in Poland under conditions of crisis.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 114-121